UKURAN PERUSAHAAN, PERPUTARAN PERSEDIAAN, DAN KEBIJAKAN DIVIDEN: PENGARUHNYA TERHADAP PERTUMBUHAN LABA - Elyana Wantikari; Dwi Septiani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to examine the effect of firm size, inventory turnover, and dividend policy on profit growth in Food & Beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Method: This research employs a quantitative approach using multiple linear regression analysis based on secondary data obtained from the companies' annual financial statements. A total of 85 observations were selected using a purposive sampling technique. Results: The findings indicate that dividend policy has a significant effect on profit growth, while firm size and inventory turnover do not show a statistically significant effect. These results support signaling theory, suggesting that a consistent dividend policy can serve as a positive signal to investors regarding the financial stability of a company. This study highlights the importance of dividend policy in profit planning and recommends that future research consider other internal and external variables that may influence profitability across various industrial sectors. Keywords: Profit Growth, Firm Size, Inventory Turnover, Dividend Policy